UPAYA PENYIDIKAN DALAM PELAKSANAAN PENETAPAN TERSANGKA - Dwi Putri Melati (KEADILAN PROGRESIF, 2021)
The Indonesian National Police are given the authority to carry out investigations. To realize an objective investigation and investigation process, especially in the determination of a suspect in the National Police institution, it must be supported by the quality of professional and modern Polri personnel in order to generate public trust in Polri in uncovering criminal acts that occur in the community. This is related to the legal process and the determination of the suspect. In order to determine a suspect or to improve the legal process from investigation to investigation level, a case title is necessary. in accordance with Article 31 paragraph (1) and paragraph (2) of the National Police Chief Regulation Number 6 of 2019 concerning Criminal Investigation.